Heat Shock Response of the Active Microbiome From Perennial Cave Ice - Mondini, Antonio; Anwar, Muhammad Zohaib; Ellegaard-Jensen, Lea; Lavin, Paris; Jacobsen, Carsten Suhr; Purcarea, Cristina (Frontiers in Microbiology, 2022)
IIce caves constitute newly investigated frozen and secluded model habitats for evaluating the resilience of ice-entrapped microbiomes in response to climate changes. This survey identified the total and active prokaryotic and eukaryotic community from millennium-old ice accumulated in Scarisoara cave (Romania) using shotgun Illumina sequencing of rRNA and mRNA-based functional analysis of the metatranscriptome. Also, the response of active microbiome to heat-shock treatment mimicking the environmental shift during ice melting was evaluated at both taxonomic and metabolic levels. The putatively active microbial community was dominated by bacterial taxa belonging to Proteobacteria and Bacteroidetes, highly resilient to thermal variations, while the scarcely present archaea belonging to Methanomicrobia was majorly affected by heat-shock. Among eukaryotes, the fungal rRNA community was shared between the resilient Chytridiomycota and Blastocladiomycota, and the more sensitive Ascomycota and Basidiomycota taxa. A complex microeukaryotic community highly represented by Tardigrada and Rotifera (Metazoa), Ciliophora and Cercozoa (Protozoa) and Chlorophyta (Plantae) was evidenced for the first time in this habitat. This community showed a quick reaction to heat-shock followed by a partial recovery after prolonged incubation at 4⁰C due to possible predation processes on the prokaryotic cluster. Analysis of mRNA differential gene expression revealed the presence of an active microbiome in the perennial ice from Scarisoara cave, and associated molecular mechanisms for coping with temperature variations by upregulation of genes involved in enzyme recovery, energy storage, carbon and nitrogen regulation, and cell motility. This first report on the active microbiome embedded in perennial ice from caves and its response to temperature stress provided a glimpse into the impact of glaciers melting and resilience mechanisms in this habitat, contributing to the knowledge on the functional role of active microbes in frozen environments and their response to climatic changes.